2018
DOI: 10.1523/eneuro.0377-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Size and Shape of Synapses in the Juvenile Rat Somatosensory Cortex with 3D Electron Microscopy

Abstract: Changes in the size of the synaptic junction are thought to have significant functional consequences. We used focused ion beam milling and scanning electron microscopy (FIB/SEM) to obtain stacks of serial sections from the six layers of the rat somatosensory cortex. We have segmented in 3D a large number of synapses (n = 6891) to analyze the size and shape of excitatory (asymmetric) and inhibitory (symmetric) synapses, using dedicated software. This study provided three main findings. Firstly, the mean synapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
83
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(117 citation statements)
references
References 74 publications
29
83
4
1
Order By: Relevance
“…Most synapses presented a simple, macular shape (accounting for 86% of the synapses in all layers of CA1), in agreement with previous reports in different brain areas and species (12,(33)(34)(35)(36).…”
Section: Shape and Size Of The Synapsessupporting
confidence: 92%
See 1 more Smart Citation
“…Most synapses presented a simple, macular shape (accounting for 86% of the synapses in all layers of CA1), in agreement with previous reports in different brain areas and species (12,(33)(34)(35)(36).…”
Section: Shape and Size Of The Synapsessupporting
confidence: 92%
“…Considering all synapses, excitatory contacts were larger than inhibitory ones, as has also been observed in layer II of the human transentorhinal cortex (11); however, this contrasted with the findings in the somatosensory cortex (36) and SR of CA1 in the rat (Blazquez-Llorca et al, in preparation). A tendency towards axodendritic synapses being bigger than axospinous synapses was also observed; however, this difference was only significant in the case of SLM synapses.…”
Section: Shape and Size Of The Synapsesmentioning
confidence: 72%
“…Previous studies of cortical synapses have found a continuum of synapse sizes (Arellano et al , 2007) that is well-modeled by a log-normal distribution (Loewenstein, Kuras and Rumpel, 2011;de Vivo et al , 2017;Santuy et al , 2018) . Even researchers who report bimodally distributed synapse size in hippocampus (Spano et al , 2019) still find log-normally distributed synapse size in neocortex (de Vivo et al , 2017) by the same methods.…”
Section: Binary Latent Statesmentioning
confidence: 99%
“…We used the map to identify constraints on the learning algorithms employed by the cortex. Previous cortical studies modeled a continuum of synapse sizes (Arellano et al , 2007) by a log-normal distribution (Loewenstein, Kuras and Rumpel, 2011;de Vivo et al , 2017;Santuy et al , 2018) . A continuum is consistent with most neural network models of learning, in which synaptic strength is a continuously graded analog variable.…”
mentioning
confidence: 99%
“…To assess changes in synaptic organization and connectivity associated with nicotine‐seeking and its modulation by exercise, we performed an ultrastructural examination of asymmetric (excitatory) and symmetric (inhibitory) synapses and their postsynaptic profiles (i.e., location on dendritic shafts or spines) within the NAc core and shell using electron microscopy (Harris & Weinberg, ). We focused on changes in the density and length of synapses based on longstanding evidence showing that the lengthening of the synapse, and thus the postsynaptic density (PSD), is associated with a proportional increase in the probability of neurotransmitter release, the number of docked synaptic vesicles and postsynaptic receptors, and the size of spine heads—all of which are markers of synaptic strength (Bourne & Harris, ; Harris & Stevens, ; Meyer, Bonhoeffer, & Scheuss, ; Mulholland & Chandler, ; Santuy, Rodríguez, DeFelipe, & Merchán‐Pérez, ; Yasumatsu, Matsuzaki, Miyazaki, Noguchi, & Kasai, ). Based on the findings with nicotine and cocaine (Alcantara et al., ; Ferrario et al., ; Gipson, Reissner, et al., ), we hypothesized that increased nicotine‐seeking following abstinence would be associated with markers predictive of synaptic potentiation (e.g., increase in the length and/or density of excitatory synapses), and that exercise during abstinence would reverse these adaptations.…”
Section: Introductionmentioning
confidence: 99%